ACCOUNTING FOR SUSTAINABILITY: WHAT NEXT? A RESEARCH AGENDA - Cunningham Gary M.; Fagerstrom Arne; Hassel Lars G. (Annals of the University of Oradea: Economic Science, 2011)
This working paper responds to increasing calls for more and different forms of accounting research involvement in accounting for sustainability. It seeks to provide background, clarify the accounting research issues, and suggest research methods. The background analysis indicates that accounting for sustainability must go beyond supplemental reporting of ecological and social information to include such emerging issues as integrated reporting of sustainability information along with financial reporting. Additional emerging issues are needs of users of sustainability reports, auditing and other assurance of sustainability information, and sustainability implications of financial failure, accounting and auditing failures, and lack of enforcement. Analysis of integrated reporting against traditional financial accounting theory concepts of the purpose of financial reporting and the postulates of going concern, reporting entity, monetary unit, and time period, indicates a need for substantial changes in the traditional financial accounting model if sustainability issues are to be integrated. The agenda concludes with five research issues and methods: - An accounting research framework for sustainability using general systems theory approaches that have been useful for similar emerging issues. - Reporting of sustainability information which has been the focus of most research to date, and the emerging important topic of integrated reporting. - Users of sustainable information, their uses and perceived needs, an area that has been largely neglected in research to date. - Auditing and assurance issues that are taking on greater importance as more users demand assurance for sustainability information. Issues include standards to be used and users expectations and reactions. - Financial distress and sustainability consequences of accounting and enforcement failures that are just now being recognized as sustainability issues.